Immunoassays using polypeptide conjugate binders with tuned affinity. (October 2010) - Leung, Ken Cham Fai; Ho, Ho Pui; Kwan, Yiu Wa; Kong, Siu Kai
Evaluation of: Albrecht C, Fechner P, Honcharenko D et al. A new assay design for clinical diagnostics based on alternative recognition elements. Biosens. Bioelectron. 25(10), 2302–2308 (2010). This article focuses on a novel concept regarding the use of polypeptide conjugates as high-affinity binders to recognize targets in immunoassays. The polypeptide conjugate binder is a hybrid molecule in which a small recognition ligand is covalently linked to a synthetic polypeptide, which binds to a protein target of interest with high affinity and selectivity. Affinity of the polypeptide conjugate to its target can be tuned by changing the length of the aliphatic spacer in between the small recognition ligand and the polypeptide. Other pros and cons of this new approach for protein recognition and sensing are compared with other immunoassays such as ELISA, the bio-barcode assay and the aptamer-based barcode assay. It is anticipated that there will be more innovation and integration using new materials and technologies to provide novel ways to detect disease markers.